2004
DOI: 10.1158/0008-5472.can-03-2224
|View full text |Cite
|
Sign up to set email alerts
|

Role of Carbonic Anhydrase IX in Human Tumor Cell Growth, Survival, and Invasion

Abstract: Carbonic anhydrase IX (CAIX) is a membrane-associated carbonic anhydrase (CA), strongly induced by hypoxia. CAIX is overexpressed in a variety of tumor types and associated with increased metastasis and poor prognosis. An inhibitor of CAs, acetazolamide has been reported to inhibit invasion. We used RNA interference (RNAi) to examine the function of CAIX in MDA468 and MDA231 breast carcinoma cells, which express high levels of CAIX under hypoxia. Hypoxia-induced CA activity was completely blocked by specific R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
208
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(225 citation statements)
references
References 15 publications
12
208
0
5
Order By: Relevance
“…This idea is consistent with the findings that the catalytic activity of CA IX is regulated by hypoxia and suggests that the capacity of CA IX to modulate pH is vital for the survival of hypoxic tumour cells. The latter suggestion has been indirectly supported also by RNAi experiments by Robertson et al (2004). However, it is also possible that the AS protein released to the culture medium can modulate spheroid formation via binding to the transport unrelated receptor and stimulate or block signal transduction in autocrine or paracrine fashion.…”
Section: Discussionmentioning
confidence: 84%
“…This idea is consistent with the findings that the catalytic activity of CA IX is regulated by hypoxia and suggests that the capacity of CA IX to modulate pH is vital for the survival of hypoxic tumour cells. The latter suggestion has been indirectly supported also by RNAi experiments by Robertson et al (2004). However, it is also possible that the AS protein released to the culture medium can modulate spheroid formation via binding to the transport unrelated receptor and stimulate or block signal transduction in autocrine or paracrine fashion.…”
Section: Discussionmentioning
confidence: 84%
“…Carbonic anhydrase isozyme IX is involved in maintaining the extracellular pH (Ivanov et al, 2001) by catalysing the reversible chemical reaction in which carbon dioxide is hydrated to carbonic acid and further to bicarbonate (Wykoff et al, 2000;Brennan et al, 2006). Thus, it is an important enzyme for cancer cells in hypoxic and normoxic conditions (Wykoff et al, 2000;Robertson et al, 2004) in the regulation of acid-base balance (Hilvo et al, 2007). Interestingly, in CRC samples studied by cDNA microarray (Talvinen et al, 2006), CA9 was found to be the most upregulated gene.…”
mentioning
confidence: 99%
“…CA-9 also has been used as a marker of tumor hypoxia, and studies have indicated that it is important in tumor growth and survival. 7 There are at least 2 members of the HIF-a family that share close sequence homology. Although studies have shown that the majority of solid tumors express nuclear HIF-1a, HIF-2a is expressed less frequently.…”
mentioning
confidence: 99%